CHALLENGES AND PERSPECTIVES OF THE NEUROPSYCHOPEDAGOGUE’S PERFORMANCE IN THE FACE OF MATHEMATICAL LEARNING DIFFICULTIES - Nogueira , Ana Paula Leite Viana; Cubas, Daniela Maria do Amaral; da Silva, Elizegina Luiz; Almeida , Karina da Conceição; Moraes, Ana Carla Costa Santana; Júnior , João Ferrera Lins; da Silva , Renata Pontes; Pinheiro , Ana Patrícia de Oliveira Ribeiro Silva; Musser , Paula Maria Grave; Ferreira, Zuelide Brotas; Fonseca , Raquel de Santana; Melo, Adriana Soely André de Souza (Seven Editora, 2024)
The present study aimed to present and analyze works that address the role of the neuropsychopedagogue in the face of mathematical learning difficulties. To this end, we used qualitative and bibliographic research using Google Scholar as a search platform, delimiting the period of the last 10 years (2013-2023), based on the descriptors: "mathematics difficulty", "mathematical learning difficulty", "mathematics and the role of the neuropsychopedagogue", with the contribution of theorists such as, Rosa (2022), Brazilian Society of Neuropsychopedagogy (SBNPp) (2021), Silveira (2023), among others. DOI:https://doi.org/10.56238/sevened2024.037-041